Metal-Free 1,2,3-Triazole Synthesis in Deep Eutectic Solvents - Sebest, Filip; Haselgrove, Samuel; White, Andrew J. P.; Díez-González, Silvia (Synlett, 2020)
The metal-free regioselective preparation of 1,5- and 1,4-disubstituted triazoles is reported through a cycloaddition–elimination sequence. Reactions were carried out in environmentally friendly deep eutectic solvent (DES) and pure products were isolated without the need for chromatographic techniques.
Keywords: alkene; azide; deep eutectic solvent; triazole; triazoline; metal-free synthesis